A Consensus Study of the Grading and Typing of Intraductal Papillary Mucinous Neoplasms of the Pancreas. Issue 4 (April 2019) - Furukawa, Toru; Fukushima, Noriyoshi; Itoi, Takao; Ohike, Nobuyuki; Mitsuhashi, Tomoko; Nakagohri, Toshio; Notohara, Kenji; Shimizu, Michio; Tajiri, Takuma; Tanaka, Mariko; Yamaguchi, Hiroshi; Yanagisawa, Akio; et al.
Abstract : Objective: The grading and typing of intraductal papillary mucinous neoplasms (IPMNs) of the pancreas are challenging for pathologists. We aimed to clarify the points of consistency and disagreement in assessing the grades and types of IPMNs. Methods: Digital slide images of 20 IPMNs were independently assessed by 10 Japanese pathologists, who then held a consensus meeting to discuss the points of disagreement and develop a consensus and recommendations. Results: The average agreement rates for grade and type were 83.5% (range, 100%–40%) and 82.5% (range, 100%–50%) and the Fleiss' κ values were 0.567 and 0.636, respectively. Conclusions: The disagreement points and recommendations were as follows: destructed ductal walls with desquamated neoplastic epithelia or mucin lakes partially lined with neoplastic cells could be invasion; intraductal stromal invasion could be dismissed unless vascular or lymphatic invasion existed; elastica staining may help visualize ducts in colloidal nodules; high-grade can be distinguished from low/intermediate grade by marked nuclear disarrangements and complex architecture in the intestinal papillae; oncocytic papillae are characterized by eosinophilic cells with round disoriented nuclei; high-grade gastric papillae can be distinguished from pancreatobiliary papillae by relatively low but complex architecture; and the most dysplastic papillae should be used to assess type in mixed papillae types. Abstract : Supplemental digital content is available in the text.